2022
DOI: 10.1039/d2ra05550c
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of effect of radiation induced crosslinking on the properties of flattened carbon nanotubes

Abstract: Molecular dynamics simulation of functionalized flattened carbon nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…A previously studied nanotube and amorphous carbon model with cross-links reduced the tensile strength of the nanotubes to ∼30 N/tex for the largest level of cross-linking of ∼20% . A more recent model of multilayer graphene that included corresponding vacancy defects near the sites of cross-links between the layers, mimicking defects produced by radiation, reported a strength decrease of ∼50% from 140 to 70 GPa at a reasonable but high cross-linking of 5% . Also worth noting is that because the strength of the junction depends on the strength of the smaller weaker nanotube, the excess mass of the larger nanotube is essentially wasted.…”
Section: Resultsmentioning
confidence: 99%
“…A previously studied nanotube and amorphous carbon model with cross-links reduced the tensile strength of the nanotubes to ∼30 N/tex for the largest level of cross-linking of ∼20% . A more recent model of multilayer graphene that included corresponding vacancy defects near the sites of cross-links between the layers, mimicking defects produced by radiation, reported a strength decrease of ∼50% from 140 to 70 GPa at a reasonable but high cross-linking of 5% . Also worth noting is that because the strength of the junction depends on the strength of the smaller weaker nanotube, the excess mass of the larger nanotube is essentially wasted.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this comparative study, the authors indicated that only C-2013 [125] and any other ReaxFF parameter sets published after 2013 (table 1) are suitable for studies of the elastic properties of materials with sp 2 carbon atoms. The ReaxFF method was also applied to investigate the mechanical response of a model of flattened CNT represented as layered graphene [161]. The presented results showed a significant impact of the irradiation-induced chemical crosslinking on the mechanical response despite a possible loss of the [82] with permission from the Royal Society of Chemistry (c) and (d) are pristine and bi-crystalline graphene in graphene/polyethylene system (e) and (f) are isolated flat pristine and wrinkled bi-crystalline graphene.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Structures of point defects bridging a graphene bilayer, (a) interstitial, (b) Frenkel pair 1, (c) Frenkel pair 2, and (d) divacancy V2, and extended defects formed by interacting holes comprising (e) 16 vacancies (V16) and (f) 30 vacancies (V30) forming one cross-link. The structure in (c) was optimized with ReaxFF .…”
mentioning
confidence: 99%
“…This variability is believed to be related to the specific morphological changes caused by the energetic electrons and γ-rays at various dosages. The molecular junctions and cross-links created between CNTs can be beneficial because they can augment the weak shear interactions between adjacent CNTs . At the mesoscale, these links can dramatically enhance the mechanical load transfer within and between CNT bundles.…”
mentioning
confidence: 99%
See 1 more Smart Citation